A 5 to 7‐year case series on single angulated implants installed following papilla‐sparing flap elevation. (17th February 2021) - Wessels, Retief; Cosyn, Jan; Eghbali, Aryan; De Bruyn, Hugo; Christiaens, Véronique
Abstract: Background: Bony concavities at the buccal aspect may cause a distortion between the implant axis and ideal prosthetic axis. Angulated implants can overcome this problem, yet long‐term data are lacking. In addition, papilla‐sparing incisions have been proposed to reduce tissue loss, yet aesthetic outcomes have not been published. Purpose: To evaluate the 5 to 7‐year outcome of single angulated implants installed following papilla‐sparing flap elevation. Materials and Methods: Patients who had been consecutively treated with a single angulated implant (Co‐axis®, Southern Implants, Irene, South Africa) in the anterior maxilla were re‐examined after 5 to 7 years. Available data at 1 year (T1) were compared to those obtained at 5 to 7 years (T2). Results: Twenty out of 22 treated patients (11 females, 9 males, mean age of 52) with 22 implants attended the 5 to 7‐year reassessment. All implants survived and stable clinical conditions could be reached with mean marginal bone loss of 1.28 mm at T2. Papilla‐sparing flap elevation resulted in Pink Esthetic Score of 9.83 at T1 and 8.23 at T2 ( p = 0.072). Mucosal Scarring Index was 4.61 at T1 and 3.50 at T2 ( p = 0.165). The overall appearance of scarring significantly improved over time ( p = 0.032), yet 59% of the cases still demonstrated scarring at T2.c Conclusions: Within the limitations of the study, angulated implants (Co‐axis®, Southern Implants) reached stable clinical conditions. Papilla‐sparing incisions may not be recommended in aesthetically demanding patients due to high risk of scarring.